Comparison between parents’ and patients’ satisfaction level towards cleft management using Cleft Evaluation Profile - Lau, Kim Lian; Ong, Siang Ching; Wan Sulaiman, Wan Salina (IIUM Journal of Orofacial and Health Sciences, 2021)
Cleft lip and palate (CLP) are common birth defects that occur in approximately 1 out of every 611 newborn in Malaysia. Cleft Evaluation Profile (CEP) is a well-established method used to evaluate the patient’s level of satisfaction with the CLP treatment that they received. This study aimed to compare the level of satisfaction of cleft patients and their parents towards cleft management in Kelantan, Malaysia. The results showed that the mean scores of CEP for the parents were between 2.04 and 3.00, whilst the patient’s mean score ranged from 2.01 to 3.04. In general, nose is the most dissatisfied feature for both patients and parents with the mean score of 3.04 for patients and 3.00 for parents. Teeth was the second highest (2.97) mean scores rated by parents but it was the third highest (2.84) mean score from the patients. Lip feature scored the third highest mean score for parents, and it was the second-highest mean score for patients. Hearing was the lowest mean score for both parents and patients. Both parties were aware of the features of their facial and nose appearance. From the weighted Kappa statistic, both the parent and patient pairs demonstrated good to very good agreement for their satisfaction towards the clinical outcome. In conclusion, features related to facial appearance (nose, teeth, lip and facial profiles) require more attention and improvement during the treatment process.